A Model for Developing the Competency of Active Learning Experience Management for Teachers to Promote Analytical thinking and Problem-solving Skills of Early Childhood Based on Professional Learning Community (PLC) - Iamsaard, Chitaporn; Jansongsang, Phatcharin; Iamsaard, Sukit (Journal of Education Studies, Chulalongkorn University, 2024)
The purpose of this research were to 1) create a model for developing competency in active learning management for teachers in order to promote analytical thinking and problem-solving skills of early childhood, with a basis in the Professional Learning Community (PLC). 2) Evaluated the effectiveness of the developed competency development model. The sample consisted of 38 early childhood teachers recruited convenient or voluntarily, 162 early childhood children recruited by simple random sampling from a number of students which the teachers used as a model, The experimental plan was one group pretest-posttest design. Conducted in 4 phases: basic data analysis, create a draft format, test the model, and improvement. The research instruments included the questionnaire, in-depth interviews, and analytical thinking and problem-solving skills tests. Statistical analysis included the mean, standard deviation, and dependent t-test. The results revealed the following. Firstly, the model has 5 steps i.e. Plan (P), Paradigm Shift (P), Professional Learning (P), Evaluation (E), and Model Sharing (M). which is called the 3PEM Model. In addition, there was a user manual which included basic information, plans for competency development, and use of the developed model. The quality of the overall model was at the highest level. Secondly, the effectiveness of the developed competency development model is as follows: the teachers’competency in active learning management was shown to be at a higher level after using the model at a .05 level of significance, both overall and in each aspect., the early childhood children’analytical thinking and problem-solving skills after the experiment, which are significantly higher after using the model at a .05 level of significance, both overall and in each aspect. The analytical thinking aspect has a higher average value than problem solving, and users have opinions towards the overall model at a high level.